Simultaneous testing of multiple subjects in ecologically valid assessments of hearing aids and assistive listening for speech in noise and music - Taylor, Larissa (My University, 2022)
Listening effort, or the amount of cognitive effort required to listen to a sound of interest, is an important measure of hearing performance, especially for hearing aid users. Hearing loss leads to increased listening effort in noisy situations and ideally hearing aid processing would reduce this effort. The goal of the two listening effort studies were to collect multiple measures of listening effort in an ecologically valid scenario, testing the effects of background noise, reverberation, and hearing aid directional processing on listening effort and head movement. To avoid the variability introduced due to age and varying degrees of hearing loss, for this initial study young normal hearing listeners were used. Two types of directional hearing aid processing were compared to the unaided condition. Our results show an effect of background noise level and reverberation on subjective listening effort, an effect on physiological listening effort, as well as a right ear bias for head direction in increased background noise and reverberation. Hearing aid type showed a significant effect on deviation angle from the speaker on stage, that is the difference between where the subject was looking and the location of the actor speaking on stage. There was also a pattern of speech intelligibility changes with changing signal-to-noise ratio, which was different based on the type of hearing aid directional processing. In addition to listening effort and speech intelligibility, music sound quality can be greatly affected by hearing aid processing. Live music has additional challenges compared to recorded music, so ecologically valid studies during live performances are essential to fully characterize sound quality. Preliminary studies in the LIVELab and an experiment conducted during an orchestra concert showed that while music sound quality judgments are subjective and variable between subjects, those with high musical sophistication are more critical and consistent in their judgments.
Keywords: listening effort; hearing aids; music; testing